A Noteon Burden Sharing Among Creditors - Dooley, Michael (IMF Working Papers; Working Paper ;, 1992)
This paper presents a framework for evaluating the relative contributions of different creditors in cases where only partial payments can be made by the debtor country. A methodology is developed to calculate partial payments-or alternatively put-determine residual financing. By focusing on the relative seniority of creditors and expectations of the debtor's ability to repay, alternative sharing rules are quantified. The measure is based on the expected present value of payments. Creditors earning a below-market rate of return suffer a burden; creditors earning the same rate of return are said to share the burden equally.